2011
DOI: 10.7201/earn.2006.11.01
|View full text |Cite
|
Sign up to set email alerts
|

Cómo los cambios en el comportamiento del consumidor y la distribuciónafectan a la competencia de los productores y procesadores de alimentos

Abstract: This paper analyses the changing competence requirements which members of the food chain face in their pursuit of competitive advantage. Two groups of trends serve as point of departure: more dynamic and heterogeneous consumer demands, which can be analysed in terms of consumer demands for sensory, health, process and convenience qualities, and changing roles for retailers in the food chain. Based on these trends, it is argued that competencies which can increase producers' level of market orientation get incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Convenience is termed as the ease one faces while doing the transaction. Grunert (2006) found that the buyer's interest has been rising inconvenience. However, some of the researchers argued that consumers are having much more concern for availability and range of products (Jones, 2000).…”
Section: Conveniencementioning
confidence: 99%
“…Convenience is termed as the ease one faces while doing the transaction. Grunert (2006) found that the buyer's interest has been rising inconvenience. However, some of the researchers argued that consumers are having much more concern for availability and range of products (Jones, 2000).…”
Section: Conveniencementioning
confidence: 99%
“…On the other hand, consumer food choice has become a complex process as consumers are demanding higher quality products (Grunert, 2005(Grunert, , 2011. In their quest for quality, consumers are seeking viable alternatives to unhealthy, unsustainable and conventional food production.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, from a managerial perspective, companies in the food industry recognize that success in today's competitive food markets begins with understanding how product attributes influence consumers' food decision-making processes [5,6]. As Grunert (2011) [7] suggests, developing an understanding of consumers-and particularly how to manage relationships with them-can be a key competitive advantage for food companies. Unsurprisingly, then, many companies are trying to devise strategies to better understand consumers' purchasing behaviors.…”
Section: Introductionmentioning
confidence: 99%